AITPM National Traffic and Transport Conference 2018 - Nau, S Zaung (2018)
The main objective of this paper is to systematically examine primary determinants that explain both spatial and temporal variations in public transportation use in Perth. It is also to offer a comprehensive and rigorous analysis of use-determinants and develops a robust predictive model based on land use characteristics, urban form, socioeconomic conditions and public transport availability factors which can inform policymaking. It employs the data on revealed preferences derived from smart cards to analyse the variations in temporal and spatial patterns of public transport use in Perth depending on types of patrons, the origin suburbs of their journeys and the day and time of travel.